Comparative Analysis of 3D Shank Kinematics During Walking: Stroke Patients Versus Healthy Individuals - Sanghan, Thanita; Hohsoh, Nusreena; Dissaneewate, Tulaya; Chong, Desmond Y. R.; Stojanovic, Goran; Begg, Rezaul; Chatpun, Surapong (IEEE access, 2025)
This study investigated the 3-axis gait kinematics of people with stroke to healthy individuals. The specific focus was stroke effects on shank movements in the sagittal, frontal and transverse planes. Sixteen stroke patients and sixteen healthy participants walked along a 10-meter walkway at self-comfortable walking speed, with shank angular velocity measured using two gyroscopes integrated into an Inertial Measurement Unit (IMU). Gait events in all motion planes, temporal gait parameters, kinematic data, asymmetry indexes (ASI), and Bland-Altman-liked correlations were also computed. Greater diversity gait patterns were observed in stroke patients. Compared with healthy controls, stroke patients showed reduced stance time on their affected side and lower non-affected swing time, causing gait asymmetry, as reflected in higher ASIs. The stroke patients' shank exhibited limited motion in all motion planes resulting in lower angular velocity and displacement. Sagittal plane angular velocity results were validated using intra-subject comparisons that showed good agreement between limbs in healthy subjects. These empirical findings in this study provide evidence that shank-based IMUs are effective in revealing temporal-spatial gait alterations in people with stroke compared to healthy individuals which can be exploited to develop a targeted rehabilitation plan to reduce abnormalities in the stroke patient group.